Growth and enrichment responses of Agrocybe dura hyphae to single and combined pollution of cadmium and lead - AN Xin-long; ZHOU Qi-xing; LI Ting; ZHANG Ning (浙江大学学报. 农业与生命科学版)
The growth responses of Agrocybe dura hyphae to cadmium (Cd), lead (Pb) and their combined pollution were examined under the condition of plate culture, as well as the action of the hyphae bioenriching Cd and Pb in the solid potato dextrose agar medium. The mycelial growth vigor, colony diameter and dry mycelial weight were reduced respectively with the concentration augmentation of Cd and Pb in the solid medium. The results also show that bioaccumulation of Cd and Pb in hyphae of Agrocybe dura existed and their contents increased with their concentrations enhancing in the solid medium, and bioaccumulation of Pb in the hyphae was promoted while that of Cd was inhibited under combined pollution of Cd and Pb.